Hubungan Antara Tingkat Kepercayaan Diri dalam Public Speaking dengan Kualitas Penggunaan Bahasa Baku: Penelitian - Fanny Rahmasari; Christin Hutahaean; Grachya Hanna Lory Saragih; Nabila Salsabilla; Widya Agustina Naibaho (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study focuses on the inconsistency between formal linguistic competence and public speaking performance influenced by affective factors, especially self-confidence; although standard language quality (phonetics, diction, syntax, fluency) is expected in formal communication, high pressure triggers cognitive load and language simplification, resulting in decreased quality. Quantitative methods tested the causal relationship between self-confidence and spoken language quality, as well as the mediating role of speaking anxiety; results showed that self-confidence explained 50.7% of the variability in language quality, with speaking anxiety as a mediator that worsened performance under pressure. The findings emphasize the importance of strengthening psychological self-confidence and integrating affective-cognitive training, including automation and linguistic resilience strategies, to overcome psychological barriers and maintain standard language quality.